Women's Participation In Pineapple Farming In Muang District, Lampang Province, Thailand - Manond, Tippawan (1994)

(untitled)
The main purpose of this study was to determine women's level of participation in pineapple farming at Sa- Dej subdistrict in Lampang Province,Thailand. The specific objectives were:( 1) to determine women's level of participation in terms of number of hours spent on specific farm practice activities; ( 2) to determine the differential participation of women in pineapple f arming in terms of the operation they undertake in relation to their husbands; (3) to determine the relations hip between the level of participation of women in pineapple farming and some selected variables postulated by t he resource,family development and expectancy theories; ( 4) to determine the significant variables in